Pengembangan Media Pembelajaran Interaktif Dasar-Dasar Program Keahlian Menggunakan Canva Kelas X TKJ SMK Muhammadiyah 1 Salam - Rifki Thorikul Aziz; Pramudi Utomo (Department of Electronics and Informatics Engineering Education, 2025)
The research on the development of interactive learning media aims to: (1) develop learning media using canva on the basics of the class X expertise program of TKJ SMK Muhammadiyah 1 Salam, (2) find out the feasibility of using canva media in the basics of the expertise program, (3) find out the response of students from the results of the development of learning media using canva. The research method uses Research and Development (R&D) with the ADDIE development framework which consists of the analysis stage, design stage, development stage, implementation stage, and evaluation stage. The research was conducted at SMK Muhammadiyah 1 Salam with 23 students in class X TKJ. The type of data used is quantitative. Data collection was carried out through questionnaires or questionnaires using the Likert scale which was analyzed in quantitative descriptive form. The results of this study show that: (1) canva learning media is developed based on the stages of analysis, design, development, implementation, and evaluation. (2) The feasibility level of canva learning media as a result of the validation of material experts one is 85% so that it is declared very feasible, The feasibility level of canva learning media as a result of the validation of material experts two is 96% so it is declared very feasible, validation by media experts is 85% so it is declared very feasible, and the evaluation results of research respondents are 82% so it is declared very feasible. (3) The students' responses showed interest and motivation in learning using canva with a percentage of 84% with details of 37% rating 4 (very motivated), 46% rating 3 (motivated) and 1% rating 2 (less motivated), this shows the motivation and interest of students in canva learning media.